PENGARUH EFEKTIVITAS PENGENDALIAN INTERNAL, KETAATAN ATURAN AKUNTANSI DAN PERILAKU TIDAK ETIS TERHADAP KECENDERUNGAN KECURANNGAN AKUNTANSI (STUDI PADA PERUSAHAAN BADAN USAHA MILIK NEGARA DI AMBON) - Ali Amin Kalau; Stevanus Leksair (Jurnal Cita Ekonomika, 2020)
This study aims to test and analyze empirically the effect of the effectiveness of internal control, obedience to accounting rules, and unethical behavior on the tendency of accounting fraud in State-Owned Enterprises (BUMN) in Ambon City. The population of this research is employees of State-Owned Public Company in Ambon city. Data collection using a questionnaire technique (questionnaire) which was distributed to 32 respondents in this study. The analytical tool used to test the hypothesis using multiple regression models. The results of this study indicate that the effectiveness of internal control variables has an effect on the tendency of accounting fraud, adherence to accounting rules has an effect on the tendency of accounting fraud and unethical behavior also affects the tendency of accounting fraud.